Marketing Strategy to Increase Sales of Traditional Herbal Medicine at PT Mulia Utama Mandiri - Jasmine Llarasati Lashari; Tri Auri Yanti; Atika Aini Nasution (Outline Journal of Management and Accounting, 2026)
This research is in the form of descriptive research, where this research aims to find out what strategies are appropriate to be used by a company. Using a SWOT analysis, this research was conducted by a company engaged in the Marketing Services business for the NAD and Sumatra regions. Mulia Utama Mandiri. The data obtained from the results of primary data, secondary data. Some of the testing methods that are the steps of the SWOT analysis test include using the IFAS Matrix, EFAS Matrix, and SWOT Diagram. Based on the results of the assessment, the IFAS Matrix is 2.76 which means t Thus, all the results of the analysis can be concluded that. Strength is an internal situation or condition for PT Mulia Utama Mandiri at this time. The strength of PT. Mulia Utama Mandiri is by maintaining the quality of its products and also maintaining durability, a good product image and providing excellent service to consumers. The results of the SWOT analysis depicted using a SWOT diagram show that the company's condition is in a growth position and the strategies that can be carried out are market development strategies and product development strategies. Thus, the marketing strategy that can be implemented by PT. Mulia Utama Mandiri is an Aggressive Strategy, which means that the company must be able to develop existing strengths and improve and maintain existing opportunities.he strength (S) of PT. The Noble Utama is greater than the weakness (W).